Universal method for preparing precious metal high-entropy alloy aerogel

Through ultrasonic cavitation and the synergistic effect of sodium borohydride and ammonium fluoride, noble metal high entropy alloy aerogel was prepared, which solved the problems of fewer preparation methods and safety hazards of freeze-thawing methods in the existing technology, and achieved high efficiency, Safe preparation process and excellent catalytic properties.

CN119426609APending Publication Date: 2025-02-14RES INST OF CHEM DEFENSE PLA ACAD OF MILITARY SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411577995.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, there are fewer preparation methods for precious metal high-entropy alloy aerogels, which are difficult to batch promote industrial production, and the freeze-thaw method has safety hazards and cumbersome steps, which limits its industrial application.

Method used

Ultrasonic cavitation, sodium borohydride and ammonium fluoride are used to synergize the dilute metal salt solution by mixing the synergistic effect of the metal precursor solution with sodium borohydride and ammonium fluoride, and gelation of the dilute metal salt solution is triggered to form noble metal high entropy alloy aerosol glue.

Benefits of technology

It realizes the safe, fast and simple preparation of precious metal high-entropy alloy aerogel, solves the safety hazards and cumbersome problems of the existing methods, has good conductivity and catalytic performance, and is suitable for industrial applications in the field of electrocatalytics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119426609A_ABST
    Figure CN119426609A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of functional material preparation, and particularly relates to a universal method for preparing precious metal high-entropy alloy aerogel. According to the method, NaBH4 serves as a reducing agent, NH4F serves as a gel initiator, a metal salt solution serves as a metal element source, a gelation reaction is rapidly conducted through huge energy generated by the cavitation effect of an ultrasonic external field, vacuum freeze drying is conducted after a large number of times of deionized water washing is conducted, and the precious metal high-entropy alloy aerogel is universally prepared through a simple method. The prepared various precious metal high-entropy alloy aerogel has good application prospects in the field of electro-catalysis, and the problems that precious metal high-entropy alloy aerogel materials are difficult to prepare, the synthesis period is long, and the process is complicated are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional material preparation, and specifically relates to a universal method for preparing noble metal high entropy alloy aerogel. Background Art

[0002] The substantial improvement in modern industrial production levels and capabilities has promoted social progress and development, but it has also caused a series of environmental problems such as the rapid depletion of fossil fuels. In order to cope with increasingly serious environmental problems, it is urgent to improve energy conversion efficiency. Against this background, electrocatalysis has gradually developed.

[0003] Since British scholar Cantor first proposed the concept of "high entropy" in 2004 (Cantor B, Chang IT H, et al. Materials Science and Engineering: A, 2004, 375: 213-2), high entropy materials have become a hot topic in the field of materials research, providing new options for material optimization design and performance improvement. High entropy alloys, as the field where the concept of "high entropy" first appeared, have excellent mechanical properties and high temperature stability, as well as good electrical properties and catalytic properties.

[0004] Aerogel has a three-dimensional self-supporting network structure with many interconnected pores, which are mostly composed of air. Precious metal high entropy alloy aerogel is a newly discovered aerogel, which has the high porosity and three-dimensional self-supporting structure of aerogel and the excellent electrical conductivity and catalytic activity of precious metal alloys. It has the advantages of both high entropy alloys and aerogels. The more pores and specific surface area provide more active sites for precious metal alloy aerogel electrocatalysis. Compared with traditional commercial catalysts, the catalytic performance is greatly improved. While precious metal high entropy alloy aerogel has the above advantages, it also shows some shortcomings, such as fewer synthesis methods, long reaction time and expensive precious metal metal salt raw materials.

[0005] Therefore, in order to solve the above problems, it is necessary to find a simple and convenient synthetic preparation method to prepare precious metal high entropy alloys, so as to facilitate their industrial application. Professor Liu Tianxi's team proposed a freeze-thaw method. By quick freezing with liquid nitrogen and then thawing, they successfully prepared five- to nine-element high entropy alloy aerogels for CO2RR. The catalytic effect was significant, which increased the production of formic acid and provided a new platform for electrochemical CO2RR (HJLi, HGHuang, et al. Adv. Mater. 2023, 35, 2209242). However, since the liquid nitrogen quick freezing step of the freeze-thaw method has great safety hazards and is cumbersome, the long gelation time also limits its large-scale promotion to industrialization, making it difficult to further industrialize.

[0006] Therefore, it is necessary to develop a universal method for preparing noble metal high entropy alloy aerogels to solve the above technical problems. Summary of the invention

[0007] The purpose of the present invention is to provide a universal method for preparing noble metal high entropy alloy aerogel, through the cavitation effect of ultrasonic wave, sodium borohydride and ammonium fluoride, the noble metal high entropy alloy aerogel is universally prepared in a safe, fast and simple way, so as to solve the problem that there are few methods for preparing noble metal high entropy alloy aerogel and it is difficult to promote it to industrial production in batches.

[0008] In order to achieve the above object, the present invention adopts the following technical scheme:

[0009] In a first aspect, the present invention provides a universal method for preparing noble metal high entropy alloy aerogel, which specifically includes the following:

[0010] 1) dissolving five or more metal precursors in water, adding sodium borohydride and ammonium fluoride and mixing them evenly, so that the total molar concentration of the metal elements in the metal precursor solution is in the range of 0.5 mmol / L-60 mmol / L;

[0011] The molar ratio of the total mole of metal elements to ammonium fluoride is 1:5 to 1:15; the molar ratio of the total mole of metal elements to sodium borohydride is 1:15 to 1:30;

[0012] The metal precursor includes a water-soluble salt, acid, base or oxide of gold, palladium, indium, platinum, nickel, rhodium or ruthenium, wherein the molar ratio of any two metal elements is 1:0.9 to 1:1.1, and any two metal precursors do not react in water;

[0013] Sodium borohydride is added as a strong reducing agent, and ammonium fluoride is added as a gel inducer. The two can synergistically trigger the gelation of dilute metal salt solutions. The driving force is the salt generated in situ during the reduction process, which increases the strength of the ions in the solution and provides a stable ligand environment.

[0014] 2) placing the mixed solution obtained in step 1) into an ultrasonic machine for thorough ultrasonication;

[0015] During this process, the intense ultrasound produced cavitation, which then showed local heating effect and intense stirring effect, greatly promoting the occurrence and progress of the gelation reaction, so that the sample could form a uniform hydrogel film in advance;

[0016] 3) allowing the mixed solution obtained in step 2) to stand at room temperature to form a uniform hydrogel film;

[0017] Due to the self-healing function of hydrogel in water environment, the hydrogel film can be well aggregated into blocks after shaking;

[0018] 4) washing the product obtained in step 3) with water to remove the residue therein;

[0019] 5) The product obtained in step 4) is quickly frozen with liquid nitrogen, and then placed in a vacuum freeze dryer for vacuum drying. After drying, a noble metal high entropy alloy aerogel is obtained.

[0020] Preferably, in step 1), the types of gold, palladium, indium, platinum, nickel, rhodium and ruthenium metal precursors include tetrachloroauric acid, sodium tetrachloropalladate, hexachloroplatinic acid, rhodium chloride, ruthenium trichloride, indium trichloride and nickel acetate.

[0021] Furthermore, in the step 1), the molar ratios of the metal ions are equal.

[0022] Preferably, in step 2), the ultrasonic power is 400-800W, and the ultrasonic time is 15-20min.

[0023] Preferably, in step 3), the standing time is 5h-8h.

[0024] Preferably, in step 4), the washing times are 4-5 times and the duration is 2-3 days.

[0025] Preferably, in step 5), the product obtained in step 4) is rapidly frozen with liquid nitrogen, and the freezing time is not less than 10 minutes.

[0026] Furthermore, the cold trap temperature of the vacuum freeze dryer is not higher than -80°C, and the drying time is 12h-24h.

[0027] In a second aspect, the present invention provides a noble metal high entropy alloy aerogel prepared by the method described in the first aspect.

[0028] In a third aspect, the present invention provides an application of the noble metal high entropy alloy aerogel as a catalytic reduction reaction catalyst or an electrocatalytic reaction catalyst.

[0029] Beneficial effects of the present invention:

[0030] The noble metal high entropy alloy aerogel prepared by the present invention has the excellent electrical conductivity and catalytic properties of high entropy alloys, the high porosity and three-dimensional self-supporting structure of the aerogel, and has high stability, and has good application prospects in the field of electrocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 X-ray diffraction test curves of samples obtained in Example 1, Example 2 and Comparative Example 1;

[0032] Figure 2 This is a scanning electron microscope photo of the sample obtained in Example 1;

[0033] Figure 3 This is a scanning electron microscope photo of the sample obtained in Example 2;

[0034] Figure 4 This is a scanning electron microscope photo of the sample obtained in Comparative Example 1;

[0035] Figure 5 This is a photo of the energy spectrum test of the sample obtained in Example 1;

[0036] Figure 6 This is a photo of the energy spectrum test of the sample obtained in Example 2;

[0037] Figure 7 This is a high-magnification transmission electron microscope lattice fringe photograph of the sample obtained in Example 1;

[0038] Figure 8 This is a high-magnification transmission electron microscope lattice fringe photograph of the sample obtained in Example 2;

[0039] Fig. 9 is the nitrogen adsorption-desorption curve of the sample obtained in Example 1;

[0040] Fig.10 is the nitrogen adsorption-desorption curve of the sample obtained in Example 2;

[0041] Fig.11 These are the LSV linear sweep voltammetry test curves of the oxygen evolution reaction of the samples obtained in Example 1, Example 2 and Comparative Example 1 under an acidic environment. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below through specific embodiments, but the protection scope of the present invention is not limited thereto.

[0043] Example 1

[0044] Measure 29.4 ml of deionized water into a 50 ml glass bottle, add the mixed metal salt solution into the glass bottle and stir evenly to obtain a metal precursor mixed solution, then add sodium borohydride and ammonium fluoride, and ultrasonicate for 15 minutes at a power of 600 W in an ultrasonic machine. After standing for 5 hours, a uniform hydrogel film is obtained; the obtained hydrogel film is washed 5 times, and then vacuum freeze-dried to obtain a noble metal high entropy alloy aerogel.

[0045] The mixed metal salt solution is a mixture of tetrachloroauric acid trihydrate, sodium tetrachloropalladate, hexachloroplatinic acid, rhodium chloride trihydrate, anhydrous ruthenium trichloride, and indium trichloride trihydrate. The molar ratio of metal ions in the six metal salts is 1:1:1:1:1:1. The total concentration of metal elements in the metal salt solution is 2.0 mmol / L. Every 0.06 mmol of the metal salt mixed solution corresponds to 0.6 mmol of ammonium fluoride and 44.3 mg of sodium borohydride.

[0046] The cold trap temperature of the above vacuum freeze drying is -80°C and the drying time is 12h.

[0047] Example 2

[0048] Measure 29.4 ml of deionized water into a 50 ml glass bottle, add the mixed metal salt solution into the glass bottle and stir evenly to obtain a metal precursor mixed solution, then add sodium borohydride and ammonium fluoride, ultrasonicate for 17 min at a power of 600 W in an ultrasonic machine, and let stand for 8 h to obtain a uniform hydrogel film;

[0049] The obtained hydrogel film was washed 5 times and vacuum freeze-dried to obtain the noble metal high entropy alloy aerogel.

[0050] The mixed metal salt solution is a mixture of tetrachloroauric acid trihydrate, sodium tetrachloropalladate, hexachloroplatinic acid, rhodium chloride trihydrate, anhydrous ruthenium trichloride, indium trichloride tetrahydrate, and nickel acetate. The molar ratio of metal ions in the seven metal salts is 1:1:1:1:1:1:1:1. The total concentration of metal elements in the metal salt solution is 2.0 mmol / L.

[0051] Each 0.06 mmol of the metal salt mixed solution corresponds to 0.6 mmol of ammonium fluoride and 44.3 mg of sodium borohydride. The cold trap temperature of the vacuum freeze drying is -80°C, and the drying time is 18 hours.

[0052] Comparative Example 1

[0053] Measure 29.4 ml of deionized water into a 50 ml glass bottle, add the metal salt solution into the glass bottle and stir evenly to obtain a metal precursor solution, then add sodium borohydride and ammonium fluoride, ultrasonicate at a power of 600 W for 20 min in an ultrasonic machine, and let stand for 10 h to obtain a uniform hydrogel film;

[0054] The obtained hydrogel film was washed 4-5 times and then freeze-dried in vacuum to obtain the gold aerogel.

[0055] The concentration of the metal salt solution is 2.0 mmol / L. The metal salt solution is tetrachloroauric acid trihydrate.

[0056] The cold trap temperature of the above vacuum freeze drying is -80°C and the drying time is 24h.

[0057] Test Results

[0058] The crystal structure, pore structure characteristics, surface morphology and catalytic activity of the obtained noble metal high entropy alloy aerogel for oxygen evolution reaction in acidic environment were determined by using D8 ADVANCE X-ray diffractometer (XRD) and German ZEISS GeminiSEM 300 scanning electron microscope (SEM).

[0059] Figure 1 X-ray diffraction test curves of samples obtained in Example 1, Example 2 and Comparative Example 1;

[0060] Figure 2 This is a scanning electron microscope photo of the sample obtained in Example 1; Figure 3 This is a scanning electron microscope photo of the sample obtained in Example 2; Figure 4 This is a scanning electron microscope photo of the sample obtained in Comparative Example 1; Figure 5 This is a photo of the energy spectrum test of the sample obtained in Example 1; Figure 6 This is a photo of the energy spectrum test of the sample obtained in Example 2; Figure 7 The LSV linear sweep voltammetry test curves of the oxygen evolution reaction in an acidic environment of the samples obtained in Example 1, Example 2 and Comparative Example 1 are shown.

[0061] Will Figure 1 The X-ray diffraction test pattern shown is compared with the standard colorimetric card, proving the successful synthesis of the FCC structural alloy.

[0062] pass Figure 2 to Figure 6 The scanning electron microscopy and energy spectrum results shown in the figure show that the sample surface has many defects and evenly distributed pores on the surface, which proves the successful synthesis of the aerogel structure and that the synthesized sample has a good morphology.

[0063] Figure 7 and Figure 8 As shown in the lattice fringes obtained by transmission electron microscopy, it can be seen that there are more crystal planes on the lattice, so the sample has better catalytic performance.

[0064] Fig. 9 and Fig.10 The figure shows the nitrogen adsorption-desorption curve of the sample. The sample has a large specific surface area and can provide more reaction sites.

[0065] Fig.11 This is the LSV linear sweep voltammetry test curve of the oxygen evolution reaction of the sample in an acidic environment. Through data processing, it is concluded that the overpotential of Example 1 is 248 mV, the overpotential of Example 2 is 273 mV, and the overpotential of Comparative Example 1 is 336 mV, indicating that the catalytic performance of the oxygen evolution reaction of the noble metal high entropy alloy aerogel in an acidic environment is much higher than that of the single metal aerogel.

[0066] From the above characterization results, it can be seen that the prepared samples have good pore structure and crystallinity. The aerogel surface contains a large number of defects, which provide more reactive sites and have stable and excellent catalytic activity for oxygen evolution reaction in acidic environment. In the electrocatalytic test of oxygen evolution reaction in 0.5M H2SO4 electrolyte environment, the minimum overpotential can reach 238mV, and it has the possibility of further optimization. .

[0067] The above description is only a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent transformation using the contents of the present invention specification or application to other related technical fields under the concept of the present invention is within the patent protection scope of the present invention.

Claims

1. A universal method for preparing noble metal high entropy alloy aerogel, characterized in that: The details include: 1) dissolving five or more metal precursors in water, adding sodium borohydride and ammonium fluoride and mixing them evenly, so that the total molar concentration of the metal elements in the metal precursor solution is in the range of 0.5 mmol / L-60 mmol / L; The molar ratio of the total mole of metal elements to ammonium fluoride is 1:5 to 1:15; the molar ratio of the total mole of metal elements to sodium borohydride is 1:15 to 1:30; The metal precursor includes water-soluble salts, acids, bases or oxides of gold, palladium, indium, platinum, nickel, rhodium or ruthenium, wherein the molar ratio of any two metal elements is 1:0.9 to 1:1.1; 2) placing the mixed solution obtained in step 1) into an ultrasonic machine for thorough ultrasonication; 3) allowing the mixed solution obtained in step 2) to stand at room temperature to form a uniform hydrogel film; 4) washing the product obtained in step 3) with water to remove the residue therein; 5) The product obtained in step 4) is quickly frozen with liquid nitrogen, and then placed in a vacuum freeze dryer for vacuum drying. After drying, a noble metal high entropy alloy aerogel is obtained.

2. The universal method for preparing noble metal high entropy alloy aerogel according to claim 1, characterized in that: In the step 1), the types of gold, palladium, indium, platinum, nickel, rhodium and ruthenium metal precursors include tetrachloroauric acid, sodium tetrachloropalladate, hexachloroplatinic acid, rhodium chloride, ruthenium trichloride, indium trichloride and nickel acetate.

3. The universal method for preparing noble metal high entropy alloy aerogel according to claim 1, characterized in that: In the step 1), the molar ratios of the metal ions are equal.

4. The universal method for preparing noble metal high entropy alloy aerogel according to claim 1, characterized in that: In the step 2), the ultrasonic power is 400-800W, and the ultrasonic time is 15-20 minutes.

5. The universal method for preparing noble metal high entropy alloy aerogel according to claim 1, characterized in that: In the step 3), the standing time is 5h-8h.

6. The universal method for preparing noble metal high entropy alloy aerogel according to claim 1, characterized in that: In the step 4), the washing times are 4-5 times and the duration is 2-3 days.

7. The universal method for preparing noble metal high entropy alloy aerogel according to claim 1, characterized in that: In the step 5), the product obtained in the step 4) is rapidly frozen with liquid nitrogen, and the freezing time is not less than 10 minutes.

8. The universal method for preparing noble metal high entropy alloy aerogel according to claim 7, characterized in that: The cold trap temperature of the vacuum freeze dryer is no higher than -80°C, and the drying time is 12h-24h.

9. A noble metal high entropy alloy aerogel prepared by the method according to any one of claims 1 to 8.

10. Use of the noble metal high entropy alloy aerogel according to claim 9 as a catalytic reduction reaction catalyst or an electrocatalytic reaction catalyst.